A study of pain, peripheral neuropathy and psychosocial late effects in multiple myeloma patients. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Cachia, Elaine; Eiser, Christine; Ezaydi, Youssef; Greenfield, Diana; Ahmedzai, Sam; Snowden, John
Abstract : Background: While intensive and novel treatments have significantly extended life expectancy in multiple myeloma, the cumulative impact of disease and treatment related factors on quality of life in relapsed patients is poorly characterised. Aims: To define the spectrum of quality of life, fatigue, pain, peripheral neuropathy and work disability affecting patients living with advanced relapsed myeloma. Methods: The authors prospectively recruited patients with myeloma who had undergone intensive management of myeloma and had received at least one subsequent treatment for progressive disease. Patients were assessed for generic (SF-12) and cancer specific (EORTC) health related quality of life parameters, pain (BPI-SF), peripheral neuropathy (s-LANSS), and concerns (adapted from the Profile of Concern's Questionnaire). Results: 32 patients (median age 61 years) participated: median duration from diagnosis was 5.5 years (range 2–12) and the median number of lines of previous treatment was 3 (range 2-6). The majority (69%) of patients were on regular analgesia. Despite stable disease, ongoing fatigue and pain were predominant symptoms. Pain had a predominantly neuropathic element in half of the cohort. Other features of neuropathy, paraesthesiae and sensory loss, were also common. Physical functioning scores were highly correlated with pain (r=−0.671; p=0.001) and QoL (r=0.576; p=0.001) and fatigue (r=−0.558; p=0.001). Social functioning was also compromised and patients reported dwelling on their current and future illness, worried of recurrence and shortened lifespan. Work disability was reflected by a fall in active or recent employment from 72 to 44% from diagnosis to the date of assessment. Conclusion: The late effects of myeloma and its treatments result in compromised quality of life with fatigue, pain, peripheral neuropathy and functional disability despite disease control with modern therapy. Models for comprehensive care of myeloma should actively address physical and social quality of life in this expanding population of patients.